Nanotechnology: Principles and Practices - Kulkarni, Sulabha K. (Springer, 2015)
Over the past 15 years, the scientific world has witnessed a dramatic interest in nanotechnology with research contributions from physicists, chemists, biologists as well as scientists working in the medical, agricultural, textile and environmental fields. The varied inputs from different disciplines and their complementary nature in the synthesis, characterization, understanding and applications from household items to space technologies have enriched the nanotechnology basics. This can be easily understood as about 80 journals have emerged on nanotechnology and hundreds of thousands of papers have been published in the last 12 years or so. Lecturers aware of this fact naturally want to introduce the new knowledge to the young generation and prepare their students for the great challenges of sustainable management of energy, water and environment faced by mankind. The availability of a large number of books, review articles and journals on nanotechnology is essential in order to get an overall picture of such a vast field, which is a very difficult task. Particularly in the case of beginners in the field as well as students at the graduate level, the complex terminologies can prevent them from exploring the fascinating world of nanotechnology. This book makes an attempt to introduce students, teachers and research scientists trying to enter the vast field of nanotechnology to nanosynthesis and various analysis methods and applications in a simple way, without overlooking the necessary principles underlying nanoscience. Continual attempts have been made right from the first edition (2006) to cover the contemporary ideas in the field. Due to the fast growth in the field by the launch of the second edition (2011), some more synthesis and analysis techniques which were becoming popular and newly discovered phenomena and effects were added to the basic contents of the first edition.